Where Were Court Cases Heard in Northern Iberia in the Early Middle Ages and Were These Community Places? - Davies, Wendy (Reti Medievali Rivista, 2023)
There is some good, though limited, evidence of community space in northern Iberia in the later tenth century. These are the spatial zones defined by the remit of local meetings at which business was transacted. There is no evidence that court cases were heard at such meetings. Rather, court cases were held at places associated with kings, and places associated with powerful landowners and churches. All of these places were used by their own proper communities whereas for court cases they were used by a temporary judicial community that was convened to deal with a case. As ever, communities were multiple and overlapping, and different communities could use community space.